Di ciò che non c'è: "Scienza del mito" e "cultura di destra" in Furio Jesi - Manfra, Enrico (Studi e materiali di storia delle religioni, 2018)
The present paper deals with the relationship between the "science of myth" and "right-wing culture" in Furio Jesi's (1914-1980) works and intellectual biography. The article describes Jesi's point of view on the presence of metaphysical and political backgrounds in the academic work of some important historians of religion, i. e., Károly Kerényi, Mircea Eliade and Georges Dumézil. The article also summarizes Jesi's epistemological approach concerning the scientific study of myth and mythology, with a particular focus on the concept of what he called the "mythological machine" as well as on his activity as literary critic and essayist.